2018
DOI: 10.1016/j.jtcvs.2018.06.090
|View full text |Cite
|
Sign up to set email alerts
|

Estimating postoperative left ventricular volume: Identification of responders to surgical ventricular reconstruction

Abstract: Adding surgical ventricular reconstruction to coronary artery bypass grafting could reduce the mortality risk by increasing ejection fraction for those with a postoperative end-systolic volume index within a specific range. The postoperative end-systolic volume index could demarcate responders to surgical ventricular reconstruction, and its estimation can help in surgical decision making.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“…Wakasa et al 5) reported in their retrospective multicenter study that adding SVR to CABG could provide a survival benefit by increasing the LV ejection fraction (LVEF) for those with postoperative LVESVI within a specific range (postoperative LVES-VI of 40 ml/m 2 to 80 ml/m 2 ).…”
Section: Volumementioning
confidence: 99%
“…Wakasa et al 5) reported in their retrospective multicenter study that adding SVR to CABG could provide a survival benefit by increasing the LV ejection fraction (LVEF) for those with postoperative LVESVI within a specific range (postoperative LVES-VI of 40 ml/m 2 to 80 ml/m 2 ).…”
Section: Volumementioning
confidence: 99%
“…4 To confer an advantage, therefore, surgery must reach a target volume. In this issue of the Journal, Wakasa and coauthors 5 report the results of the Surgical Ventricular Reconstruction for Severe Ventricular Dysfunction registry (SURVIVE). In this multicenter study, 17 different hospitals in Japan collected data for patients with heart failure and left ventricular systolic dysfunction.…”
Section: Lorenzo a Menicanti MDmentioning
confidence: 99%
“…Patients with same volume have different outcomes according to ejection fraction. The goal of Wakasa and coauthors 5 was to identify which patients can respond to the surgery, and they generated 2 equations predicting postoperative volume and ejection fraction.…”
Section: Lorenzo a Menicanti MDmentioning
confidence: 99%
“…First described by Cooley in 1958, surgical ventricular reconstruction promised improvements in LV volumes, ejection fraction, functional class, and even survival. 1,2 Since then, a variety of techniques, with and without cardiopulmonary bypass, have been described. [2][3][4] Onohura and colleagues 5 report the results of an experimental trial of an LV shaping device used in a rat model of ischemic cardiomyopathy.…”
mentioning
confidence: 99%
“…1,2 Since then, a variety of techniques, with and without cardiopulmonary bypass, have been described. [2][3][4] Onohura and colleagues 5 report the results of an experimental trial of an LV shaping device used in a rat model of ischemic cardiomyopathy. In their model, ischemic cardiomyopathy was induced via ligation of the coronary artery.…”
mentioning
confidence: 99%